1970
DOI: 10.1111/j.1471-0528.1970.tb03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital Candidas1s and Oral Contraceptives

Abstract: Summary In spite of contrary reports this study confirms the view of the majority of workers that the incidence of candidial vulvo‐vaginitis is not greater in women who take the contraceptive pill than in those who do not and shows that with the combined type of oral contraceptive the dose of oestrogen or convertible progestogen is more important than their relative amounts in contributing to the presence of Candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The importance of this yeast as a potential pathogen of the female genital tract has been stressed in a number of studies of its incidence in different population groups (Morris and Morris, 1967 ; Carroll et al, 1973; Hurley etal., 1973). The present investigation and those of Rohatiner and Grimble (1970) and Oriel et al (1972) have revealed that the incidence of candidal infection among non-pregnant patients attending special treatment clinics is much higher than in other groups of non-pregnant patients. One reason for the increase could be the transmission of the infection from an uncircumcised male partner, the chance of such infection being higher in the promiscuous patient.…”
Section: Discussionsupporting
confidence: 64%
“…The importance of this yeast as a potential pathogen of the female genital tract has been stressed in a number of studies of its incidence in different population groups (Morris and Morris, 1967 ; Carroll et al, 1973; Hurley etal., 1973). The present investigation and those of Rohatiner and Grimble (1970) and Oriel et al (1972) have revealed that the incidence of candidal infection among non-pregnant patients attending special treatment clinics is much higher than in other groups of non-pregnant patients. One reason for the increase could be the transmission of the infection from an uncircumcised male partner, the chance of such infection being higher in the promiscuous patient.…”
Section: Discussionsupporting
confidence: 64%
“…In recent years the incidence of monilial involvement has been reported to be increasing due to a wider use of the contraceptive pill (Catterall, 1971). Catterall found that 49.5% of the patients with candidiasis were taking the pill, which correlated well with the 50% found by Gardner (1965) although the association has been refuted by others (Rohatiner and Grimble, 1970). Due to the difficulty, in general practice, of deciding which organism is the cause of the vaginitis or whether, in fact, it is due to a mixed infection it is helpful to use a broad spectrum therapy; this is particularly so in practices where laboratory facilities are not readily available.…”
supporting
confidence: 73%
“…This is probably due to the use of contraceptives with a low hormonal content. In most investigations in which Candida infection was positively correlated with the use of oral contraceptives, preparations with higher hormonal content were involved (Yaffee and Grots, 1965;Porter and Lyle, 1966;Catterall, 1966); the hormonal content has been shown to be of importance for the presence of Candida (Rohatiner and Grimble, 1970).…”
Section: Resultsmentioning
confidence: 99%